Windows Phone 7 made simple - Westfall, Jon.; SpringerLink (United States Apress, 2011)
Looks at the features and functions of the Windows Phone 7 series, covering such topics as making phone calls, using email, setting up and using Facebook and Twitter, security, browsing the Web with Internet Explorer, using Microsoft Office mobile, and connecting to Zune software
pt. 1. Quick start guide -- pt. 2. Introduction --pt. 3. You and your Windows Phone 7.
Electronic reproduction.
Keywords: Windows phone (Computer software).; Cell phones; Digital music players; Pocket computers; Electronic books; Smartphones; Electronic books